Spatio-Temporal Variation of Physico-Chemical Parameters in Wasai Reservoir, Kano State - Shehu, A. H; Ismail, F. M; Umar, U. H.; Muhammad, A. M; Muhammad, A. M.; Idris, J. A.; Mairami, F. M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
The present study assessed the physico-chemical parameters variation in Wasai reservoir with the aim of providing current information on the water quality for agricultural and domestic usage. Water samples were collected from four different sampling stations and the physico-chemical parameters were analyzed using standard procedures. The data obtained were analyzed using analysis of variance with Duncan’s New Multiple Range Test used to separate significant means at 5% level. Data were compared with recent reports by World Health Organization and FEPA permissible limits for aquatic water quality. The result obtained revealed no significant difference in water surface temperature (27.20 oC) and pH (8.49) for the period of ten months. However, significant difference (P≤0.05) in the EC ((151.33-252.00 µS/cm), Total Dissolved Solids (TDS) (162.67-242.00 mg/L) and BOD (2.25-8.57 mg/l) were found among the sampling locations with variation in months. The EC, TDS, DO and BOD values in all the locations were above their permissible limits (pH= 6.5-8.5; EC= 1000 µS/cm; 1000 mg/L).